A Comparison Of the Cognitive Development of 3–6 year-old Children who Receive Family-Supported Preschool Education, Institutional Education and no Education - (:unkn) unknown (SAGE Publications Ltd, 2010)
This study aims to examine the effects of Family Supported Preschool Education programs on the development of preschool children. By measuring the effects of family-supported preschool education on cognitive development, this study helps support alternative methods of making preschool education more widespread. The study uses the experimental model. The cognitive development of 3–6 year-old preschool children who did not undergo any education, who received institutional education, and family-supported education was compared against the Marmara Development Inventory. The first two groups were not given any special treatment, while the group receiving family-supported education was given cognitive education by the researcher through one-to-one support. The effectiveness of this program was investigated. The study group comprised a total of 173 children aged between 3 and 6 years and residing in Gaziantep between the academic years 2005–2007. Among these children, 56 did not receive any preschool education, 58 were attending an official preschool affiliated to the Ministry of Education, and 59 were receiving family-supported preschool education. The results from this two-year study were analysed by using the SPSS 11,0 package program. The results showed that family-supported education contributed to children's cognitive development in all age groups (36–48 months, 49–60 months, 61–72 months). It was also found that not having received any preschool education, having a mother who received education in child development, and the income level of the family are all variables which affect cognitive development. On the other hand, parental education levels, parental jobs, sex of the children, and the number of siblings were found to be not effective in children's cognitive development. In sum, family-supported education was found to be effective. © 2010 A B Academic Publishers Printed in Great Britain.